Aplikasi Perencanaan Obat Berbasis Web Menggunakan Metode Rapid Application Development (RAD) Di Dinas Kesehatan Kabupaten Banyuwangi - Shodiq, Moh. Nur; Fitriya, Aida; Haq, Endi Sailul; Rini, Eka Mistiko (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
Drug planning in drug procurement activities is less monitored by the Banyuwangi Health Office which affects the availability of drugs at the Banyuwangi Regency Health Office. The purpose of this research is to avoid overlapping drug stocks at the Banyuwangi Health Office because drugs are one of the problems at the Banyuwangi Regency Health Office. Drug planning is one of the important and decisive aspects of drug management drug planning and health supplies are a decisive start in drug management. In Banyuwangi Regency, drug planning still uses manual methods. This can trigger the length of drug data collection which ends up delaying drug planning, this triggers researchers to use this research method using the Rapid Application Development (RAD) method with the initial stage, namely designing needs by conducting direct interviews and reviewing data to obtain information about drug planning in the Banyuwangi Regency Health Office.In the process of developing this web-based drug planning application, it is hoped that it can minimize overlapping drug stocks between the Banyuwangi Regency Health Office and Puskesmas so that drug planning can be neatly arranged. The testing conducted by the researcher is Black Box Testing. By using this method, the developer can ensure that the system developed meets the functional and operational requirements of the users.